Laminate, gasket and fuel cell

By using a heat sealant of amorphous polyester polyol, epoxy resin and isocyanate compounds in the gasket member of the fuel cell, the problem of insufficient humidity resistance of the heat sealant in the prior art under high temperature and high humidity environment is solved. , achieving efficient gas sealing and long-term stable performance.

CN115706238BActive Publication Date: 2025-02-25DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210929675.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-05
Filing Date
2022-08-03
Publication Date
2025-02-25
Estimated Expiration
2042-08-03

AI Technical Summary

Technical Problem

In fuel cells, the heat sealant of the gasket member needs to withstand high temperature and high humidity environments, and the prior art is difficult to provide a heat sealing layer with excellent humidity resistance and suitable for use in fuel cells.

Method used

Using a heat sealant containing amorphous polyester polyol (A), an epoxy resin (B) and isocyanate compound (C), the heat sealing layer is formed through the reaction products of these materials to ensure that it is under high temperature and high humidity conditions. stability.

Benefits of technology

A heat sealing layer with excellent humidity resistance is realized, and the leakage of fuel gas and oxidant gas can be prevented for a long time and stably under a high temperature and high humidity environment, and the area where the catalyst layer is not formed is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115706238B_ABST
    Figure CN115706238B_ABST
Patent Text Reader

Abstract

The present invention provides a fuel cell gasket laminate having a heat seal layer with excellent moisture and heat resistance and suitable for a fuel cell gasket, a gasket, a membrane electrode assembly having the gasket, and a fuel cell. The laminate comprises a substrate and a heat seal layer disposed on the substrate, the heat seal layer is a reaction product of a heat seal agent comprising an amorphous polyester polyol (A), an epoxy resin (B), and an isocyanate compound (C), the amorphous polyester polyol (A) is a reaction product of a polycarboxylic acid and a polyol, the amount of aromatic polycarboxylic acid in the polycarboxylic acid is 95% by mass or more, and the glass transition temperature of the amorphous polyester polyol (A) is above -20°C and below 40°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate, a gasket, a membrane electrode assembly and a fuel cell. Background Art

[0002] In recent years, fuel cells have attracted much attention as a countermeasure to environmental and energy issues. A fuel cell is a battery that converts chemical energy generated by the oxidation of reducing gases such as hydrogen and methane using oxidizing gases such as oxygen and air into electrical energy. It is considered a clean energy source because the raw materials are abundant and the only waste generated by power generation is water.

[0003] Fuel cells are classified into alkaline type, phosphoric acid type, polymer type, molten carbonate type, solid oxide type, etc. according to the type of electrolyte. Among them, polymer electrolyte fuel cells (PEFC) are low-temperature operation, high output density, and can be small and lightweight, so they are expected to be used as portable power sources, household power sources, and vehicle power sources. Polymer electrolyte fuel cells have a structure in which a fuel electrode (anode catalyst layer) is provided on one surface of a polymer electrolyte membrane and an air electrode (cathode catalyst layer) is provided on the other surface in a facing manner. This is called a membrane electrode assembly.

[0004] During power generation, a fuel gas containing hydrogen is supplied to the fuel electrode side, and an oxidant gas containing oxygen is supplied to the air electrode side. The supplied fuel gas becomes protons and electrons in the anode catalyst layer (also referred to as the fuel electrode catalyst layer or simply referred to as the electrode catalyst layer, or catalyst layer). Protons move to the cathode catalyst layer (also referred to as the air electrode catalyst layer, or simply referred to as the electrode catalyst layer or catalyst layer) side through the polymer electrolyte and polymer electrolyte membrane in the anode catalyst layer. Electrons travel through an external circuit and also travel to the cathode catalyst layer. In the cathode catalyst layer, protons, electrons and the oxidant gas supplied from the outside react to generate water. As described above, chemical reactions occur in the fuel electrode and the air electrode, generating electric charges and functioning as a battery.

[0005] Generally, in a membrane electrode assembly, a gasket member is provided outside the catalyst layer on the electrolyte membrane to prevent gas leakage caused by a difference in thickness between a region where a catalyst layer is formed and a region where a catalyst layer is not formed on the electrolyte membrane, and concentrated degradation of the region where a catalyst layer is not formed. The gasket member can be bonded to the electrolyte membrane by a heat sealant (Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2007-66768 Summary of the invention

[0009] Problems to be solved by the invention

[0010] In a fuel cell, hydrogen and oxygen react with heat to generate water. Therefore, the heat sealant that joins the gasket member to the electrolyte membrane must be able to withstand use under high temperature and high humidity. That is, the purpose of the present application is to provide a fuel cell gasket laminate, a gasket, a membrane electrode assembly having the gasket, and a fuel cell having excellent moisture and heat resistance and a heat seal layer suitable for a fuel cell gasket.

[0011] Means for solving problems

[0012] The present invention relates to a laminate, comprising a substrate and a heat-sealing layer arranged on the substrate, wherein the heat-sealing layer is a reaction product of a heat-sealing agent comprising an amorphous polyester polyol (A), an epoxy resin (B) and an isocyanate compound (C), the amorphous polyester polyol (A) is a reaction product of a polycarboxylic acid and a polyol, the amount of aromatic polycarboxylic acid in the polycarboxylic acid is 95% by mass or more, and the glass transition temperature of the amorphous polyester polyol (A) is above -20°C and below 40°C.

[0013] Effects of the Invention

[0014] According to the present invention, a fuel cell gasket laminate having excellent moisture and heat resistance and including a heat seal layer suitable for a fuel cell gasket, a gasket, a membrane electrode assembly including the gasket, and a fuel cell can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram showing a configuration example of a solid polymer fuel cell according to an embodiment of the present invention.

[0016] Description of Reference Numerals

[0017] 1: Electrolyte membrane 2: Anode electrode 3: Cathode electrode 4, 4': Gasket 5, 5': Gas diffusion layer 6: Anode side 7: Cathode side 8, 8': Gas flow path 9, 9': Cooling water flow path 10, 10': Spacer 11: Polymer electrolyte fuel cell 12: Membrane electrode assembly DETAILED DESCRIPTION

[0018] <Laminate>

[0019] (Base material)

[0020] The present invention has a substrate and a heat seal layer disposed on the substrate. As the substrate, it is envisaged that it is used as a gasket of a fuel cell, and preferably a film that is not easily deformed even when pressure is applied. Films comprising polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide, polyimide, silicone rubber, fluororubber, etc. can be cited. They can be used alone, or two or more types can be stacked and used. As an example, the film thickness of the substrate is more than 10 μm and less than 200 μm, which is set to an appropriate value in view of the film thickness of the catalyst layer and the diffusion layer described later.

[0021] (Heat seal layer)

[0022] The heat seal layer is provided on the substrate and is a coating film of a reaction product of a heat seal agent including an amorphous polyester polyol (A), an epoxy resin (B), and an isocyanate compound (C).

[0023] The amorphous polyester polyol (A) is a reaction product of a polycarboxylic acid and a polyol, wherein the amount of the aromatic polycarboxylic acid in the polycarboxylic acid is 95% by mass or more, and the glass transition temperature is -20°C to 40°C.

[0024] In addition, the glass transition temperature in the present invention refers to a value measured as follows.

[0025] Using a differential scanning calorimeter (DSC-7000 manufactured by SII Nano Technology Co., Ltd., hereinafter referred to as DSC), 5 mg of the sample was heated from room temperature to 200°C at 10°C / min under a nitrogen flow of 30 mL / min, and then cooled to -80°C at 10°C / min. The temperature was raised to 150°C at 10°C / min again, and the DSC curve was measured. The intersection of the straight line obtained by extending the baseline on the low temperature side of the measurement result observed in the second heating process to the high temperature side and the tangent line drawn at the point where the slope of the curve of the step-shaped part of the glass transition reaches the maximum was taken as the glass transition temperature, and the temperature at this time was taken as the glass transition temperature. In addition, the temperature was raised to 200°C in the first heating, but this only needs to be the temperature at which the polyester polyol (A) is fully melted, and it is appropriately adjusted when 200°C is insufficient. Similarly, the cooling temperature is also appropriately adjusted when -80°C is insufficient (such as when the glass transition temperature is lower).

[0026] Whether the polyester polyol is amorphous can be determined by whether a clear crystallization peak or crystal melting peak is observed in the cooling step or the second heating step in the above-mentioned measurement method. The polyester polyol (A) used in the present invention is amorphous, so no clear crystallization peak or crystal melting peak is observed.

[0027] As the aromatic polycarboxylic acid used in the synthesis of the polyester polyol (A), there can be mentioned aromatic polycarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, phthalic anhydride, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic anhydride, naphthalene dicarboxylic acid, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, benzophenone tetracarboxylic acid, benzophenone tetracarboxylic dianhydride, 5-sodium sulfonate of isophthalic acid, tetrachlorophthalic anhydride, and tetrabromophthalic anhydride; and methyl esters of aromatic polycarboxylic acids such as dimethyl terephthalate and dimethyl 2,6-naphthalene dicarboxylate. One kind or a combination of two or more kinds can be used.

[0028] Preferably, terephthalic acid and isophthalic acid are used. In addition, from the viewpoint of reducing the crystallinity of the polyester polyol (A), among the polycarboxylic acids used in the synthesis, it is preferred that the amount of terephthalic acid is 60% by mass or less, and the amount of isophthalic acid is 40% by mass or more and 100% by mass or less.

[0029] Examples of the polycarboxylic acid that can be used in combination with the aromatic polycarboxylic acid include aliphatic polycarboxylic acids such as malonic acid, ethylmalonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, succinic anhydride, alkenylsuccinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, maleic anhydride, and itaconic acid;

[0030] Alkyl esters of aliphatic polybasic acids such as dimethyl malonate, diethyl malonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethyl pimelate, diethyl sebacate, dimethyl fumarate, diethyl fumarate, dimethyl maleate, and diethyl maleate;

[0031] Alicyclic polyacids such as 1,1-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride, nadic anhydride, chlorobridged anhydride, etc.

[0032] Examples of the polyol used in the synthesis of the polyester polyol (A) include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propylene glycol, 1,2,2-trimethyl-1,3-propylene glycol, 2,2-dimethyl-3-isopropyl-1,3-propylene glycol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, and 2,2,4-trimethyl-1,3-pentanediol.

[0033] Ether diols such as polyoxyethylene glycol and polyoxypropylene glycol;

[0034] Modified polyether diols obtained by ring-opening polymerization of the above-mentioned aliphatic diols with various compounds containing cyclic ether bonds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether;

[0035] Lactone polyester polyols obtained by polycondensation of the above-mentioned aliphatic diols with lactones, various lactones such as ε-caprolactone;

[0036] Bisphenols such as bisphenol A and bisphenol F;

[0037] Alkylene oxide adducts of bisphenols obtained by adding ethylene oxide, propylene oxide, etc. to bisphenols such as bisphenol A and bisphenol F;

[0038] Aliphatic polyols such as trimethylolethane, trimethylolpropane, glycerol, hexanetriol, pentaerythritol, etc.;

[0039] Modified polyether polyols obtained by ring-opening polymerization of the above-mentioned aliphatic polyols with various compounds containing cyclic ether bonds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether;

[0040] Lactone polyester polyols obtained by polycondensation reaction of the above-mentioned aliphatic polyols with various lactones such as ε-caprolactone, etc.

[0041] From the viewpoint of being able to form a heat seal layer having excellent heat resistance and moisture heat resistance, the polyol preferably contains 1,6-hexanediol. The blending amount of 1,6-hexanediol in the polyol is preferably 70% by mass or more.

[0042] In addition, neopentyl glycol is preferably used because it can be expected to have an effect of reducing the crystallinity of the polyester polyol (A). As an example, the amount of neopentyl glycol in the polyol is 3% by mass or more and 30% by mass or less.

[0043] The polyester polyol (A) may be a polyester polyurethane polyol which is a reaction product of a composition comprising polyisocyanates in addition to the above-mentioned polycarboxylic acid and polyol. Alternatively, it may be a polyester polyurethane polyol obtained by urethane-stretching the reaction product of the above-mentioned polycarboxylic acid and polyol using polyisocyanates. The polyisocyanates used at this time are not particularly limited, and conventionally known polyisocyanates may be used, and two or more thereof may be used alone or in combination.

[0044] Examples of the polyisocyanate include aromatic diisocyanates such as 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate (also referred to as polymeric MDI or crude MDI), 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0045] Aromatic aliphatic diisocyanates (aliphatic isocyanates having one or more aromatic rings in the molecule) such as m-xylylene diisocyanate or p-xylylene diisocyanate (alias: XDI), α, α, α', α'-tetramethylxylylene diisocyanate (alias: TMXDI),

[0046] Aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate,

[0047] alicyclic diisocyanates such as 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, isophorone diisocyanate (also known as IPDI), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatomethyl)cyclohexane,

[0048] Biuret forms, urate forms, adducts, allophanate forms, carbodiimide-modified forms, uretdione-modified forms of these diisocyanates, and urethane prepolymers obtained by reacting these polyisocyanates with polyols.

[0049] The number average molecular weight (Mn) of the polyester polyol (A) is in the range of 2,000 to 30,000, more preferably 3,000 to 15,000, and even more preferably 4,000 to 12,000. By making the number average molecular weight within this range, the cured coating film of the heat sealant can maintain appropriate flexibility and form a heat seal layer with excellent heat sealability. In addition, the viscosity of the heat sealant is not too high, and the coating property is good.

[0050] In addition, in this invention, the number average molecular weight (Mn) is a value measured by gel permeation chromatography (GPC) under the following conditions.

[0051] Measuring device: HLC-8320GPC manufactured by Tosoh Corporation

[0052] Column: TSKgel 4000HXL, TSKgel 3000HXL, TSKgel 2000HXL, TSKgel1000HXL manufactured by Tosoh Corporation

[0053] Detector: RI (differential refractometer)

[0054] Data processing: Multi Station GPC-8020modelII manufactured by Tosoh Corporation

[0055] Determination conditions: column temperature 40°C

[0056] Solvent Tetrahydrofuran

[0057] Flow rate 0.35ml / min

[0058] Standard: Monodisperse polystyrene

[0059] Sample: A tetrahydrofuran solution containing 0.2% by mass in terms of resin solid content was filtered through a microfilter (100 μl)

[0060] The hydroxyl value of the polyester polyol (A) is preferably in the range of 1 to 40 mgKOH / g, and more preferably 3 mgKOH / g or more and 30 mgKOH / g or less, from the viewpoint of more excellent adhesive strength.

[0061] The solid acid value of the polyester polyol (A) is not particularly limited, but is preferably 10.0 mgKOH / g or less. If it is 5.0 mgKOH / g or less, the wet heat resistance is more excellent, which is preferred. In addition, there is no particular limitation on the lower limit of the solid acid value, but as an example, it is 0.5 mgKOH / g or more. It can also be 0 mgKOH / g.

[0062] The blending amount of the polyester polyol (A) in the solid content of the heat sealant is preferably 20% by mass or more and 95% by mass or less.

[0063] The epoxy resin (B) is not particularly limited, and conventionally known epoxy resins can be used, including bisphenol-type epoxy resins such as bisphenol A epoxy resin and bisphenol F epoxy resin; biphenyl-type epoxy resins such as biphenyl-type epoxy resin and tetramethylbiphenyl-type epoxy resin; dicyclopentadiene-phenol addition reaction type epoxy resin, etc. These can be used alone or in combination of two or more. Among them, bisphenol-type epoxy resins are preferably used from the aspect of being able to form a heat seal layer with high adhesion to various substrates and excellent moisture and heat resistance.

[0064] The softening point of the epoxy resin (B) determined by the ring and ball method of JIS K 7234 is preferably 150° C. or lower, more preferably 60° C. or higher and 100° C. or lower.

[0065] The number average molecular weight (Mn) of the epoxy resin (B) is preferably in the range of 450 to 4,000 from the viewpoint of high adhesion to various substrates and the ability to form a heat seal layer having excellent moisture and heat resistance. The epoxy equivalent is preferably in the range of 230 to 3,300 g / equivalent.

[0066] The content of the epoxy resin (B) in the solid content of the heat sealant is preferably 1% by mass or more and 30% by mass or less.

[0067] The isocyanate compound (C) is not particularly limited as long as it is a compound having two or more isocyanate groups in one molecule, and various compounds can be used. As specific examples of the isocyanate compound (C), the same substances as the polyisocyanates exemplified as the raw materials of the polyester polyol (A) can be cited, and two or more thereof can be used alone or in combination.

[0068] In order to suppress the permeation of fuel gas or water vapor generated in the course of power generation, it is preferred to use an aromatic or aromatic aliphatic polyisocyanate or a derivative thereof.

[0069] For the isocyanate compound (C), the ratio [NCO] / [OH] of the total number of moles of hydroxyl groups [OH] contained in the heat sealant to the total number of moles of isocyanate groups [NCO] possessed by the isocyanate compound (C) is preferably 0.4 to 4.0, more preferably 0.4 to 1.4. This can form a heat seal layer having excellent heat resistance and moisture heat resistance.

[0070] The heat sealant contains an organic solvent. The organic solvent dissolves the polyester polyol (A), the epoxy resin (B), and the isocyanate compound (C) to adjust the viscosity to be suitable for coating. Examples of the organic solvent include esters such as ethyl acetate, butyl acetate, and cellosolve acetate, ketones such as acetone, methyl ethyl ketone, isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as dichloromethane and dichloroethane, dimethyl sulfoxide, and dimethylsulfonamide.

[0071] The heat sealant may contain components other than the amorphous polyester polyol (A), the epoxy resin (B), and the isocyanate compound (C).

[0072] From the aspect of being able to form a heat seal layer with better moisture and heat resistance, the heat seal agent preferably includes a resin (D) having a glass transition temperature of 50°C or more and 110°C or less. In addition, by including the resin (D), the surface tackiness of the heat seal layer described later can be suppressed, and the workability is excellent. The resin (D) can be used without particular limitation as long as the glass transition temperature is 50°C or more and 110°C or less. As an example, polyester resins, polyurethane resins, polyurea resins, acrylic resins, polyamide resins, polyimide resins, epoxy resins, rosin-modified epoxy resins, etc. are cited. Polyester resin (D1) is preferred.

[0073] As the polycarboxylic acid and polyol used in the synthesis of the polyester resin (D1), the same polycarboxylic acid and polyol as those for the amorphous polyester polyol (A) can be used. From the viewpoint of excellent moist heat resistance, the blending amount of the polycarboxylic acid in the aromatic polycarboxylic acid is preferably 95% by mass or more.

[0074] The number average molecular weight (Mn) of the polyester (D1) is preferably 3,000 to 100,000, more preferably 3,500 to 50,000, and most preferably 4,000 to 30,000. The weight average molecular weight (Mw) is preferably in the range of 5,000 to 300,000, and more preferably in the range of 10,000 to 200,000.

[0075] When the resin (D) has a hydroxyl group, its hydroxyl value is preferably in the range of 1 to 40 mgKOH / g, more preferably 3 mgKOH / g or more and 30 mgKOH / g or less. When the resin (D) has a carboxyl group, its solid content acid value is not particularly limited, but is preferably 10.0 mgKOH / g or less. If it is 5.0 mgKOH / g or less, the moisture and heat resistance is more excellent, which is preferred. In addition, there is no particular limitation on the lower limit of the solid content acid value, but as an example, it is 0.5 mgKOH / g or more.

[0076] The glass transition temperature of the resin (D) is more preferably 60° C. or higher, and more preferably 65° C. or higher. The glass transition temperature of the resin (D) is more preferably 100° C. or lower, and more preferably 90° C. or lower.

[0077] The amount of resin (D) is appropriately adjusted according to the desired degree of moisture and heat resistance, and is therefore not particularly limited. If the amount is too large, the heat sealing temperature needs to be increased. The amount is preferably 90 parts by mass or less relative to 100 parts by mass of the total of polyester polyol (A) and resin (D), more preferably 3 parts by mass or more and 80 parts by mass or less, and even more preferably 5 parts by mass or more and 65 parts by mass or less.

[0078] In the case where the heat seal layer requires initial viscosity, the heat sealant may include a tackifier. Examples of the tackifier include rosin or rosin ester tackifiers, terpene or terpene phenol tackifiers, saturated hydrocarbon resins, coumarone tackifiers, coumarone indene tackifiers, styrene resin tackifiers, xylene resin tackifiers, phenolic resin tackifiers, petroleum resin tackifiers, ketone resin tackifiers, etc. These may be used alone or in combination of two or more.

[0079] Examples of rosin or rosin esters include polymerized rosin, disproportionated rosin, hydrogenated rosin, maleic rosin, fumaric rosin, and glycerol esters, pentaerythritol esters, methyl esters, ethyl esters, butyl esters, ethylene glycol esters, diethylene glycol esters, and triethylene glycol esters thereof.

[0080] Examples of the terpene-based or terpene-phenol-based compounds include oligomeric terpene-based compounds, α-pinene polymers, β-pinene polymers, terpene-phenol-based compounds, aromatic modified terpene-based compounds, and hydrogenated terpene-based compounds.

[0081] As the phenolic resin system, a condensate of phenols and formaldehyde can be used. As the phenols, phenol, meta-cresol, 3,5-xylenol, p-alkylphenol, resorcinol, etc. can be cited, and examples thereof include resol resins obtained by adding these phenols to formaldehyde using an alkali catalyst, and novolac resins obtained by condensing these phenols using an acid catalyst. In addition, rosin phenol resins obtained by adding phenol to rosin using an acid catalyst and performing thermal polymerization can also be exemplified.

[0082] Examples of the petroleum resin system include petroleum resins obtained by polymerizing petroleum fractions having 5 carbon atoms obtained from pentene, pentadiene, isoprene, etc., petroleum resins obtained by polymerizing petroleum fractions having 9 carbon atoms obtained from indene, methylindene, vinyltoluene, styrene, α-methylstyrene, β-methylstyrene, etc., C5-C9 copolymer petroleum resins obtained from the above-mentioned various monomers and petroleum resins obtained by hydrogenating them, petroleum resins obtained from cyclopentadiene and dicyclopentadiene; and hydrogenated products of these petroleum resins; modified petroleum resins obtained by modifying these petroleum resins with maleic anhydride, maleic acid, fumaric acid, (meth)acrylic acid, phenol, etc., etc.

[0083] Examples of the ketone resin include known and commonly used ketone resins, and preferably, formaldehyde resin, cyclohexanone-formaldehyde resin, ketone-aldehyde condensation resin, and the like can be used.

[0084] The tackifier can have various softening points. From the perspectives of compatibility, color tone, thermal stability, etc. when mixed with the polyol ester polyol (A), epoxy resin (B), etc., ketone resin tackifiers having a softening point of 70 to 160° C., preferably 80 to 100° C., or rosin resins and hydrogenated derivatives thereof having a softening point of 80 to 160° C., preferably 90 to 110° C. are preferred, and ketone resin tackifiers having a softening point of 70 to 160° C., preferably 80 to 100° C. are more preferred. Ketone resin tackifiers having an acid value of 2 to 20 mgKOH / g and a hydroxyl value of 10 mgKOH / g or less and hydrogenated rosin tackifiers are preferred, and ketone resin tackifiers having an acid value of 2 to 20 mgKOH / g and a hydroxyl value of 10 mgKOH / g or less are more preferred.

[0085] When a tackifier is used, the amount thereof blended is preferably 0.1 to 10% by mass based on the solid content of the heat sealant.

[0086] From the aspect of being able to expect to improve its cohesive force and improve the effect of water vapor barrier and gas barrier, the heat sealant also preferably contains an inorganic filler. As the inorganic filler, silicon dioxide, aluminum oxide, aluminum flakes, glass flakes, etc. can be mentioned. In particular, if a plate-like inorganic compound is used, the gas barrier property is improved, so it is preferred. Examples of plate-like inorganic compounds include hydrous silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, chlorite, dickite, nacre, etc., antigorite, chrysotile, etc.), pyrophyllite-talc group (pyrophyllite, talc, cerolite, etc.), montmorillonite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, spheneite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, micas such as phlogopite, nacreous mica, tetrasilicon mica, taenia mica, etc.), chlorite group (lithophore, sudosite, clinochlore, oolite, nickel chlorite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The plate-like inorganic compound may be used alone or in combination of two or more.

[0087] The plate-like inorganic compound may be an ionic plate-like inorganic compound having an electric charge between layers, or a nonionic plate-like inorganic compound having no electric charge. The presence or absence of electric charge between layers will not directly have a significant impact on the gas barrier properties of the heat seal layer. However, ionic plate-like inorganic compounds and inorganic compounds that are swellable in water have poor dispersibility in organic solvents. If the amount added is increased, the heat sealant will increase in viscosity or become thixotropic, and the coating adaptability may be reduced. Therefore, it is preferred that the plate-like inorganic compound has no interlayer charge and is nonionic.

[0088] The average particle size of the plate-like inorganic compound is not particularly limited. As an example, it is preferably 0.1 μm or more, and more preferably 1 μm or more. If it is less than 0.1 μm, the circuitous path of the oxygen molecule will not become longer, and the improvement of the gas barrier properties cannot be fully expected. The upper limit of the average particle size is not particularly limited. If the particle size is too large, defects such as stripes sometimes occur on the coating surface depending on the coating method. Therefore, as an example, the average particle size is preferably 100 μm or less, preferably 20 μm or less. It should be noted that in this specification, the average particle size of the plate-like inorganic compound refers to the particle size with the highest frequency of occurrence when the particle size distribution of the plate-like inorganic compound is measured using a light scattering measuring device.

[0089] In order to improve the gas barrier properties based on the labyrinth effect of oxygen, the aspect ratio of the plate-like inorganic compound is preferably high. Specifically, it is preferably 3 or more, more preferably 10 or more, and most preferably 40 or more.

[0090] When an inorganic filler is used, the amount thereof blended is preferably 5 to 50% by mass, more preferably 20 to 40% by mass, based on the solid content of the heat sealant.

[0091] The heat sealant may further include other ingredients, such as wax, filler and other lubricants, defoamers, plasticizers, leveling agents, emulsifiers, dispersion stabilizers, surfactants, preservatives, antibacterial agents, rust inhibitors, antioxidants, curing catalysts, light stabilizers, ultraviolet absorbers, photocatalytic compounds, dyes, inorganic pigments, organic pigments, body pigments, antistatic agents, etc.

[0092] The laminate of the present invention is formed by providing a heat seal layer on a substrate. The coating method of the heat sealant is not particularly limited, and as an example, gravure coating, reverse coating, kiss coating, air knife coating, Meyer rod coating, roller coating, dip coating, etc. can be cited.

[0093] A heat sealant is applied to a substrate, and after the solvent is dried, it is cured to form a heat seal layer. The drying temperature is 50 to 180°C, and the drying time is about 0.5 seconds to 1 minute. The drying method is not particularly limited, and as an example, hot air drying can be cited. The curing temperature is room temperature to 90°C, and the curing time is 2 days to 2 weeks.

[0094] The amount of the heat sealant applied (solid content) is not particularly limited, but is, for example, 1.0 to 30.0 g / m 2 . Preferably 5.0 to 25.0 g / m 2 , more preferably 7.0 to 20.0 g / m 2 .

[0095] <Gasket, fuel cell>

[0096] The laminate of the present invention is suitable for use as a gasket for a fuel cell. Figure 1 Schematic diagram showing the structure of a fuel cell 11 according to one embodiment of the present invention. Figure 1 As shown, the fuel cell 11 has a battery unit in which a membrane electrode assembly 12 is sandwiched between a set of spacers 10, 10'. The battery unit may also be a stacked structure in which the spacers 10, 10' are untied and a plurality of them are stacked in series. The membrane electrode assembly 12 has an electrolyte membrane 1, an anode electrode 2, a cathode electrode 3, gaskets 4, 4' and gas diffusion layers 5, 5'.

[0097] The electrolyte membrane 1 is not particularly limited as long as it is made of a material with high ionic conductivity, and perfluorosulfonic acid-based or hydrocarbon-based solid polymer electrolyte membranes are mostly used. Specifically, examples include Nafion (registered trademark) of DuPont, Goreselect (registered trademark) manufactured by Japan Gore Co., Ltd., Flemion (registered trademark) manufactured by Asahi Glass Co., Ltd., and the like. The thickness of the electrolyte membrane 10 is not particularly limited, but is preferably 10 μm to 200 μm. If it is thinner than this, it is likely to be damaged and difficult to handle. If it is thicker than this, the membrane resistance increases, causing problems in performance.

[0098] The anode electrode 2 and the cathode electrode 3 contain a catalyst and an electrolyte. As the catalyst, for example, particles containing platinum group elements such as platinum, palladium, ruthenium, iridium, rhodium, and osmium, metals such as iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, and aluminum, or their alloys, oxides, and complex oxides are used. From the viewpoints of activity and stability, the particle size is preferably about 0.5 nm or more and 20 nm or less.

[0099] The catalyst particles may be used alone, but are preferably used by being supported on a conductive carrier. As the conductive carrier, carbon particles are generally used, but there is no particular limitation as long as they are particulate and have conductivity and chemical resistance. Examples include carbon black, graphite (Japanese: gerafaito), graphite (Japanese: kokuen), activated carbon, carbon fiber, carbon nanotube, fullerene, and the like. The particle size of the carbon particles is preferably about 10 to 1000 nm. If it is smaller than this, it is difficult to form an electron conduction path. If it is larger than this, the thickness of the anode electrode 2 and the cathode electrode 3 increases, and the resistance increases.

[0100] The electrolyte used for the anode electrode 2 and the cathode electrode 3 only needs to have ionic conductivity. If a material homogeneous with the electrolyte membrane 1 is used, the adhesion between the anode electrode 2, the cathode electrode 3, and the electrolyte membrane 1 is improved, so it is preferred.

[0101] The anode electrode 2 and the cathode electrode 3 can be formed, for example, by directly wet-coating a slurry in which catalyst particles, a conductive monomer, and an electrolyte are dispersed on the electrolyte membrane 1, or by a method of transferring after coating on a transfer substrate or gas diffusion layers 5, 5'.

[0102] The solvent or dispersion medium of the slurry is not particularly limited, and may be a solvent or dispersion medium capable of dissolving or dispersing the electrolyte. Water, alcohols (methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 3-butanol, pentanol, ethylene glycol, diacetone alcohol, 1-methoxy-2-propanol, etc.), ketones (acetone, methyl ethyl ketone, pentanone, methyl isobutyl ketone, diisobutyl ketone, etc.), ethers (dioxane, tetrahydrofuran, etc.), sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc., may be used alone or in combination. It is preferred that a substance be easily removed by heating, and it is particularly preferred to use a substance having a boiling point of 150°C or less.

[0103] A drying step may be provided as necessary during the formation of the anode electrode 2 and the cathode electrode 3. The drying method is not particularly limited, and examples thereof include hot air drying, infrared drying, and reduced pressure drying.

[0104] The gas diffusion layers 5 and 5' are made of a member having gas permeability and electron conductivity, and can be formed of, for example, a metal member such as foamed metal or metal mesh, or a carbon member such as carbon cloth or carbon paper.

[0105] The spacers 10, 10' are made of a conductive material that is impermeable to gas, such as a metal plate subjected to corrosion resistance treatment, or a carbon-based material such as calcined carbon. The spacers 10, 10' are formed with gas flow paths 8, 8' for gas circulation, and cooling water flow paths 9, 9' for cooling water circulation are formed on the main surface opposite to the surface formed with the gas flow paths 8, 8'. The spacers 10, 10' are arranged adjacent to the gas diffusion layers 5, 5'.

[0106] Fuel gas is supplied from gas flow path 8 of separator 10 on the anode 6 side. For example, hydrogen gas is used as fuel gas. Oxidant gas is supplied from gas flow path 8' of separator 10' on the cathode 7 side. For example, gas containing oxygen such as air is supplied as oxidant gas.

[0107] The gaskets 4, 4' are composed of the laminate of the present invention and are frame-shaped. The gasket 4 is arranged between the electrolyte membrane 1 and the separator 10 in such a manner that the anode electrode 2 and the gas diffusion layer 5 are located at the opening of the gasket 4. The gasket 4' is arranged between the electrolyte membrane 1 and the separator 10' in such a manner that the cathode electrode 3 and the gas diffusion layer 5' are located at the opening of the gasket 4'. The gaskets 4, 4' are bonded to the electrolyte membrane 1 via the above-mentioned heat seal layer.

[0108] The heat seal layer of the gasket 4, 4' of the present invention has excellent moisture and heat resistance and is not easily degraded even under high temperature and high humidity conditions such as in a fuel cell, and can stably prevent leakage of fuel gas and oxidant gas and concentrated degradation of the area without a catalyst layer for a long period of time.

[0109] [Example]

[0110] Hereinafter, specific synthesis examples and embodiments are listed to further illustrate the present invention, but the present invention is not limited to these embodiments. It should be noted that, in the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0111] <Preparation of Heat Sealing Agent>

[0112] (Synthesis of polyester polyol (A))

[0113] In a flask equipped with a stirring rod, a temperature sensor, and a distillation tube, 791 parts by weight of isophthalic acid (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 339 parts by weight of terephthalic acid (manufactured by Mitsui Chemicals, Inc.), 20 parts by weight of trimellitic anhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 738 parts by weight of 1,6-hexanediol (manufactured by BASF), 107 parts by weight of neopentyl glycol (manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 4.0 parts by weight of an organic titanium compound (Orgatix TC-100 manufactured by Matsumoto Fine Chemical Co., Ltd.) were placed, and dry nitrogen was flowed into the flask while stirring, and the temperature was raised to 240° C. while distilling off the generated water. Then, an esterification reaction was carried out while increasing the vacuum degree to 30 torr, and the reaction was terminated when the resin acid value became 1.50 mgKOH / g or less, thereby obtaining a polyester polyol (A). The number average molecular weight (Mn) of the polyester polyol (A) was 7,000, the weight average molecular weight (Mw) was 23,500, the solid content hydroxyl value was 22.4 mgKOH / g, the solid content acid value was 1.26 mgKOH / g, and the glass transition temperature (Tg) was 2.1° C. The polyester polyol (A) was diluted with ethyl acetate before use.

[0114] (Synthesis of polyester polyol (AH))

[0115] In a flask equipped with a stirring rod, a temperature sensor, and a distillation tube, 310 parts by weight of sebacic acid, 420 parts by weight of isophthalic acid, 212 parts by weight of phthalic anhydride, 11.1 parts by weight of trimellitic anhydride, 610 parts by weight of neopentyl glycol, and 0.7 parts by weight of an organic titanium compound were added, and dry nitrogen was flowed into the flask while stirring, and the temperature was raised to 240°C while distilling off the generated water. Then, the esterification reaction was carried out while the vacuum degree was increased to 30 torr, and the reaction was stopped when the acid value became 2.00 mgKOH / g or less to obtain a polyester polyol (AH). The number average molecular weight (Mn) of the polyester polyol (AH) was 6,000, the weight average molecular weight (Mw) was 17,000, the solid content hydroxyl value was 14.6 mgKOH / g, the solid content acid value was 1.94 mgKOH / g, and the glass transition temperature (Tg) was 6.0°C. The polyester polyol (AH) was diluted with ethyl acetate before use.

[0116] (Synthesis of polyester (D1))

[0117] A polyester polyol was obtained by a conventional method using 697.2 parts of terephthalic acid, 72.9 parts of ethylene glycol, and 229.9 parts of 1,2-propylene glycol. The obtained polyester polyol was diluted with methyl ethyl ketone to a resin solid content of 30%, thereby obtaining a polyester (D1) having a number average molecular weight (Mn) of 8,400, a weight average molecular weight (Mw) of 61,300, a resin hydroxyl value (solid content conversion) of 5.0 mgKOH / g, a resin acid value (solid content conversion) of 4.0 mgKOH / g, and a glass transition temperature of 84°C.

[0118] (Preparation of heat sealant)

[0119] The polyester polyol (A), epoxy resin (B), isocyanate compound (C) and polyester (D1) synthesized above were mixed in the ratio shown in Table 1 to prepare heat sealants for Examples and Comparative Examples. It should be noted that all the values ​​in the table are converted to solid components (or non-volatile components). The details of the components in the table are as follows.

[0120] Epoxy resin B-1: JER1001 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent: 450-500, softening point: 64°C, number average molecular weight: 900)

[0121] Epoxy resin B-2: JER1004 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent: 875-975, softening point: 97°C, number average molecular weight: 1650)

[0122] Isocyanate compound (C): TAKENATE D-110N (manufactured by Mitsui Takeda Chemicals, Inc., trimethylolpropane adduct of xylylene diisocyanate)

[0123] <Manufacturing of Laminated Body>

[0124] The prepared heat sealant was made into 10g / m 2 The laminates of the examples and comparative examples were obtained by coating the laminates with a thickness of 25 μm on a polyethylene terephthalate film (manufactured by Toyobo Co., Ltd., E5102) in a manner such that the solvent evaporated, and then aging was performed at 60°C for 3 days. The laminates of the examples and comparative examples were obtained. Polyethylene terephthalate (manufactured by Toyobo Co., Ltd., E5102) with a thickness of 25 μm was overlapped on the heat-sealed surface of the laminates produced, and heat-sealed using a heating roller for Examples 1 and 2 and Comparative Examples 1 and 2 at 120°C, 2.0 MPa, and 15 seconds to obtain test pieces. For Example 3, heat-sealed at 150°C, 0.4 MPa, and 30 seconds to obtain test pieces.

[0125] <Evaluation>

[0126] (Heat seal strength)

[0127] The sample width was set to 15 mm, and the 180° peel strength was measured at a tensile speed of 300 mm / min. The results are summarized in Table 1. The unit is N / 15 mm.

[0128] (Moisture and heat resistance)

[0129] After the test piece was immersed in hot water at 85° C. for 500 hours, the heat seal strength was measured in the same manner as above. The results are summarized in Table 1.

[0130]

Table 1

[0131] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Polyester polyol (A) 100.0 100.0 50.0 100.0 Polyester polyol (AH) 100.0 Epoxy resin (B-1) 25.0 25.0 Epoxy resin (B-2) 25.0 Isocyanate compound (C) 8.0 8.0 4.0 8.0 4.2 Polyester (D1) 50.0 [NCO] / [OH] 0.88 0.88 0.71 0.88 0.88 Heat seal strength 4.5 2.5 0.8* 3.4 12.0 Heat and humidity resistance 8.9 7.5 PET fracture 5.6 1.7

Claims

1. A laminate comprising a substrate and a heat seal layer disposed on the substrate, The heat seal layer is a reaction product of a heat seal agent comprising a non-crystalline polyester polyol (A), an epoxy resin (B) and an isocyanate compound (C). The amorphous polyester polyol (A) is a reaction product of a polycarboxylic acid and a polyol. The amount of the aromatic polycarboxylic acid in the polycarboxylic acid is 95% by mass or more. The glass transition temperature of the amorphous polyester polyol (A) is -20°C or higher and 40°C or lower.

2. The laminate according to claim 1, wherein The blending amount of terephthalic acid in the polycarboxylic acid is 60% by mass or less, and the blending amount of isophthalic acid in the polycarboxylic acid is 40% by mass or more.

3. The laminate according to claim 1 or 2, wherein: The polyol contains 1,6-hexanediol, and the blending amount of the 1,6-hexanediol in the polyol is 70% by mass or more.

4. The laminate according to any one of claims 1 to 3, wherein The content of the amorphous polyester polyol (A) in the nonvolatile component of the heat sealant is 20% by mass or more and 95% by mass or less.

5. The laminate according to any one of claims 1 to 4, wherein The softening point of the epoxy resin (B) is 60° C. or higher and 150° C. or lower.

6. The laminate according to any one of claims 1 to 5, wherein The content of the epoxy resin (B) in the nonvolatile components of the heat sealant is 1% by mass or more and 30% by mass or less.

7. The laminate according to any one of claims 1 to 6, wherein The isocyanate compound (C) is an isocyanate compound having an aromatic ring.

8. The laminate according to any one of claims 1 to 7, wherein The ratio [NCO] / [OH] of the total number of moles of hydroxyl groups [OH] contained in the heat-sealing agent to the total number of moles of isocyanate groups [NCO] of the isocyanate compound (C) is 0.4 to 4.

0.

9. The laminate according to any one of claims 1 to 8, wherein The substrate is polyethylene naphthalate.

10. The laminate according to any one of claims 1 to 8, wherein The substrate is polyimide. 11 . A fuel cell gasket, comprising the laminate according to claim 1 .

12. A fuel cell comprising the gasket according to claim 11.

Citation Information

Patent Citations

  • Electrolyte membrane-electrode assembly and fuel cell using the same

    JP2007066768A

  • Gas barrier adhesive, film and gas barrier film

    IN201817022272A

  • Adhesive and oxygen barrier film using the same

    JP2012201731A